The sweet spots of a tennis racquet - Cross, R. (Sports Engineering, 1998)
Measurements are presented on the behaviour of a hand-held tennis racquet when it impacts with a tennis ball. It is shown that an impulse is transmitted through the racquet to the hand in about 1.5 ms, with the result that the hand and the forearm both have a strong influence on the behaviour of the racquet even while the ball is still in contact with the strings. Regardless of the impact point, the racquet head recoils as a result of the impact and an impulsive torque is applied to the hand, causing the hand to rotate about an axis through the wrist. The impulsive forces on the hand, arising from this torque, do not drop to zero for any impact point, even for an impact at either of the two sweet spots of the racquet. Forces on the hand arise from rotation, translation and vibration of the handle. For an impact at the vibration node, only the vibrational component is zero. For an impact at the centre of percussion, the net force on the hand or forearm is zero since the forces acting on the upper and lower parts of the hand are then equal and opposite.